2003
DOI: 10.4088/jcp.v64n0919
|View full text |Cite
|
Sign up to set email alerts
|

Acute and Long-Term Treatment and Prevention of Relapse of Obsessive-Compulsive Disorder With Paroxetine

Abstract: Paroxetine doses of 40 mg/day and 60 mg/day (but not 20 mg/day) are effective in treating acute obsessive-compulsive disorder. Long-term treatment with paroxetine is effective and safe, decreases the rate of relapse, and lengthens the time to relapse.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
61
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 118 publications
(63 citation statements)
references
References 0 publications
1
61
0
Order By: Relevance
“…Other Return to Week 0 Y-BOCS or CGI-S Z1 above Week 12 CGI-S [Hollander et al, 2003] .722 .21, .650…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Other Return to Week 0 Y-BOCS or CGI-S Z1 above Week 12 CGI-S [Hollander et al, 2003] .722 .21, .650…”
Section: Discussionmentioning
confidence: 99%
“…Koran et al [2002] found that sertraline (SERT) responders rarely relapsed over 28 weeks whether they were maintained on SERT (3/108; 3%) or switched over 2 weeks to PBO (5/113; 4%); relapse was defined as a Y-BOCS increase of at least five points, a total Y-BOCS score of at least 20, and at least a one-point increase on the CGI-I scale relative to the end of acute treatment at three consecutive visits at 2-week intervals. Finally, Hollander et al [2003] found that paroxetine (PAR) responders maintained on PAR for 6 months, compared to those switched immediately to placebo, had a significantly lower relapse rate (37.7 versus 58.8%) and longer time to relapse (62.9 versus 28.5 days); relapse was defined as a return to the pretreatment Y-BOCS score or an increase of at least one point on the CGI-severity (CGI-S) scale [Guy, 1976] relative to the end of treatment. In sum, using different SRIs, different study designs, and different relapse criteria, double-blind discontinuation studies found SRI relapse rates to range from a low of 4% over 28 weeks ] to a high of 89% over 7 weeks [Pato et al, 1988].…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…On the other hand, a few studies report on a doseÁresponse relationship: A larger study observed higher venlafaxine blood levels in responders compared to non-responders, but found no evidence for a relationship between treatment outcome and blood levels of paroxetine [12]. Hollander et al reported that paroxetine doses of 40 and 60 mg/day (but not 20 mg/day) are effective in treating acute obsessive-compulsive disorder [13]. Yaryura-Tobias et al indicate that doses of venlafaxine less than 225 mg/day are not effective in OCD [14].…”
Section: Discussionmentioning
confidence: 99%
“…Currently, pharmacological treatment like Serotonin Reuptake Inhibitors (SRIs) and Cognitive Behavior Therapy (CBT) are the selected treatments for OCD. Potential side effects of the drug and relapse rates (24% to 89%) are the main problems of pharmacological treatment in patients with OCD (Hollander et al, 2003;Koran, Hackett, Rubin, Wolkow, & Robinson, 2002). Relapse rate of the disease within three months after the CBT termination was higher than 50% (Simpson, Franklin, Cheng, Foa, & Liebowitz, 2005;Anand, Sudhir, Math, Thennarasu, & Reddy, 2011).…”
Section: Introductionmentioning
confidence: 98%